Pemeliharaan Dokumen Rekam Medis Rawat Jalan di Ruang Filling Unit Rekam Medis RSU Suaka Insan Banjarmasin - Husin Husin; Eka Rahma Ningsih; Noorlaili Hidayah (HB PRESS, 2022)
Function of medical record documents for hospitals is as a source of information in order to carry out planning, analysis, decision making, assessment and accountability as well as possible. In order to support the creation of successful storage, observation, and maintenance of medical record documents, it is necessary to have basic archival provisions, namely place, infrastructure, document maintenance from danger and damage. This study aimed to see the implementation of the maintenance of medical record documents in the outpatient Filing room of the medical record unit at the Suaka Insan Hospital, Banjarmasin. The method used in this research was descriptive case study. The results of the research carried out, from a number of 100 samples of medical record documents found damage to the physical aspect only as much as 7%, damage to the chemical aspect alone as much as 3%, damage to the biological aspect alone as much as 6% because the medical record document care had not been maximized by the officers.